Brand Rebranding, Brand Associations, Customer Satisfaction, Company Reputation dan Customer Loyalty - I Putu David Aritona; Ni Putu Nina Eka Lestari (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe purpose of this study was to determine the effect of corporate rebranding, on brand associations, customer satisfaction, company reputation and customer loyalty. The study was conducted at Jasindo Insurance Denpasar. The technique of collecting data uses a questionnaire to 100 customers of Jasindo Insurance Denpasar. Data were analyzed by Structure Equation Modeling data analysis with AMOS program. The results of the study show that there is corporate rebranding that has a positive and significant effect on brand associations, customer satisfaction and company reputation. Besides that there is also a positive and significant influence between corporate rebranding brand associations, customer satisfaction and the company's reputation for customer loyalty.